ENHANCEMENT OF THE CAPACITY OF MSMEs IN CURUG TOURISM VILLAGE, BOGOR REGENCY, THROUGH ACCURATE FINANCIAL BOOKKEEPING - Indupurnahayu, Indupurnahayu; Puryati, Dwi; Sparta, Sparta (LPPM Univ. Ibn Khaldun Bogor, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving economic growth, particularly at the local level. However, many MSMEs still face challenges in systematic financial management and recording, which makes it difficult to measure business performance and make informed decisions. This community service activity was conducted in Curug Tourism Village, Bogor Regency, with the aim of improving MSME capacity through training in accurate financial bookkeeping. The training employed an educational and participatory approach, covering five main topics: cash control, simple bookkeeping, calculating the cost of goods manufactured (COGS), introduction to taxation, and digital marketing. Evaluation results using pre- and post-test questionnaires showed a significant increase in participants' understanding. One of the largest improvements was seen in the ability to record transactions independently, from an average score of 2.1 to 3.9. These findings demonstrate that hands-on training can significantly strengthen financial literacy and business management skills among MSMEs.